2009
DOI: 10.1099/jmm.0.005827-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Streptococcus agalactiae strains and density of vaginal carriage

Abstract: We screened 500 pregnant women who had no risk factors for Streptococcus agalactiae vaginal carriage, and isolated 39 S. agalactiae strains (8 %). The density of carriage was low in 16 cases (41 %), intermediate in 16 cases (41 %) and heavy in seven cases (18 %). Strains were mostly of serotype III (41 %), Ia (26 %) and V (18 %). Thirty-five strains had at least one of five genetic markers that have been associated with virulent phylogenetic subgroups of strains. Using PCR, nine strains (23 %) were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
3
8
1
Order By: Relevance
“…A relatively low carriage rate obtained by culture for GBS in this study was similar to the carriage rate of 8% reported in a recent study where vaginal swabs from pregnant women were screened for GBS [28]. Ideally, both vaginal and rectal swabs are required to ensure the highest possible GBS detection rate [29].…”
Section: Discussionsupporting
confidence: 83%
“…A relatively low carriage rate obtained by culture for GBS in this study was similar to the carriage rate of 8% reported in a recent study where vaginal swabs from pregnant women were screened for GBS [28]. Ideally, both vaginal and rectal swabs are required to ensure the highest possible GBS detection rate [29].…”
Section: Discussionsupporting
confidence: 83%
“…Serotype III was the most prevalent, accounting for 63.7% of the isolates, followed by serotypes Ia (21.9%), II (9.6%), and V (4.8%). These findings are similar to previous reports from North America and Europe (9,10). Serotype Ia was significantly higher in children than in adults (42.9% versus 23%, respectively; P ϭ 0.0414) ( Table 1).…”
supporting
confidence: 82%
“…Genetic diversity among S. agalactiae isolates recovered from humans, bovine, and fish has been previously demonstrated Jafar et al 2008;Olivares-Fuster et al 2008;Suanyuk et al 2008;Pereira et al 2009;van der Mee-Marquet et al 2009;Qasem et al 2010). Evans et al (2008) demonstrated that piscine GBS from Brazil, Israel, Honduras, and the USA appeared to represent a distinct genetic population of strains that were largely unrelated to human GBS or bovine GBS.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, S. agalactiae and S. iniae are recognized as zoonotic bacteria-capable of causing diseases and mortality in humans (Weinstein et al 1997;Brodeur et al 2000;Shoemaker et al 2001;Agnew and Barnes 2007;Pombert et al 2009). Streptococcus agalactiae (also referred to as group B streptococcus [GBS]) infects a wide range of species but is commonly associated with diseases in bovine (mastitis) and humans (neonatal meningitis, sepsis, pneumonia, and osteomyelitis; Evans et al 2005;Kawamura et al 2005;Springman et al 2009;van der Mee-Marquet et al 2009) as well as fish and frogs (Wilkinson et al 1973;Amborski et al 1983). Strains from these different hosts exhibit similar whole-cell protein patterns when analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, suggesting that they have a similar ancestry (Elliott et al 1990).…”
mentioning
confidence: 99%